2018
DOI: 10.1177/0266242618775169
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of post-entry speed of internationalisation on export performance of INVs

Abstract: This paper aims to explore the under-researched topic of post-entry speed of internationalization (PSI) in the context of international new ventures (INVs). We unbundle PSI and examine its relationship with both financial and non-financial export performance, considering three related, but conceptually distinct, dimensions of PSI: internationalization intensity, spread, and geographical diversity. Building on organizational learning theory, we highlight different mechanisms that contribute to post-entry perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(121 citation statements)
references
References 161 publications
(302 reference statements)
4
115
2
Order By: Relevance
“…In particular, post‐entry internationalization speed has emerged as a new phenomenon (Sadeghi et al . 2018) that needs further empirical attention. Second, international diversification can be defined as the number of markets into which a small firm has entered (Zhang et al .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, post‐entry internationalization speed has emerged as a new phenomenon (Sadeghi et al . 2018) that needs further empirical attention. Second, international diversification can be defined as the number of markets into which a small firm has entered (Zhang et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, the antecedents of the other two dimensions (speed of international depth and breadth) are less known and require additional empirical investigation. Moreover, apart from four empirical studies by Chetty et al (2014), Hilmersson and Johanson (2016), Sadeghi et al (2018), Hilmersson et al (2017), a multidimensional perspective of small and medium-sized enterprise (SME) internationalization speed remains relatively underexplored. The first three of these studies were restricted to the examination of the relationships between speed and performance, while the fourth only studied the antecedents of speed of internationalization breadth.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the performance of born globals, Sadeghi et al (2018) affirm that the rapid international expansion offers some important financial and non-financial growth opportunities. However, to take advantage of such opportunities it is necessary to learn with the experiences, to develop new capabilities and to adapt them to new markets.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The presence of born globals is still a relatively rare phenomenon in the international market and their number has not increased significantly yet (Braunerhjelm & Halldin, 2019). Empirical studies have shown that to survive in foreign markets, born globals seek to keep their path throughout their insertion and positioning themselves in business networks (Ngasri & Freeman, 2018), developing new capabilities and adapting themselves to new markets (Sadeghi et al, 2018). For born globals from emerging economies, the international path reflects other kinds of challenges and strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation